2011
DOI: 10.1038/onc.2011.192
|View full text |Cite
|
Sign up to set email alerts
|

COP9 signalosome subunit 6 stabilizes COP1, which functions as an E3 ubiquitin ligase for 14-3-3σ

Abstract: 14-3-3σ, a gene upregulated by p53 in response to DNA damage, exists as part of a positive-feedback loop which activates p53 and is a human cancer epithelial marker downregulated in various cancer types. 14-3-3σ levels are critical for maintaining p53 activity in response to DNA damage and regulating signal mediators such as Akt. Here, we identify Mammalian Constitutive Photomorphogenic 1 (COP1) as a novel E3 ubiquitin ligase for targeting 14-3-3σ through proteasome degradation. We show for the first time that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 43 publications
2
76
0
Order By: Relevance
“…Degradation processes in the p53 pathway add additional layers of complexity because several p53-targeting E3 ligases, including MDM2 and COP1, also have autoubiquitination activity (140,141). Furthermore, genes encoding the E3 ligases COP1, MDM2, PIRH2, and JFK, all of which target p53, are induced by the transcriptional activity of p53 (138,139,(142)(143)(144).…”
Section: P53 Pathwaymentioning
confidence: 99%
“…Degradation processes in the p53 pathway add additional layers of complexity because several p53-targeting E3 ligases, including MDM2 and COP1, also have autoubiquitination activity (140,141). Furthermore, genes encoding the E3 ligases COP1, MDM2, PIRH2, and JFK, all of which target p53, are induced by the transcriptional activity of p53 (138,139,(142)(143)(144).…”
Section: P53 Pathwaymentioning
confidence: 99%
“…To evaluate whether this effect was mediated via MG132 was used to block the proteasomal degradation in Hela cells ( Okamoto et al, 2009;Choi et al, 2011;Tian et al, 2012). Our results showed that TGZ-mediated was reduced in TGZ treatment cells versus control group and apoptosis has been investigated in various cancer cells, including cervical cancer cell (Nagamine et al, 2003).…”
Section: Tgz Inhibits Ubiquitination Of P53 In Cervical Cancer Cellmentioning
confidence: 99%
“…In contrast, Csn3 appears to negatively regulate cell proliferation as its knockdown accelerates cell growth in cultured cells (20). In addition, Csn3 and Csn6 affect human COP1 levels in different ways (20,21). In Neurospora crassa, which lacks Csn8, knock-out of Csn3 results in a faster growth rate, whereas knock-out of other CSN genes reduces growth (23).…”
mentioning
confidence: 99%